Evaluation of initial live weight in fattening bulls fed diets based on Panicum maximum, peanut (Arachis hypogaea) cuticles and a protein-energy supplement - Castellón, M. E.; Elías, Arabel (Cuban Journal of Agricultural Science, 2016)
The use of peanut cuticles, Panicum maximum forage and a protein-energy supplement (MUSS-Lactibiol) was evaluated in an integral diet for bulls starting fattening. Twenty seven stabulated bulls were utilized divided in four groups (treatments A, B, C and D) with an average initial live weight of 282, 327, 364 and 422 kg ± 4 kg, respectively. Diets in the formula (% humid basis) consisted of P. maximum forage, 89, peanut cuticles, 7 and MUSS-Lactibiol, 4. The concentrate-forage relationship (% dry basis) was 21:79, with ME concentration of 10.0006 MJ.kg DM-1 and CP of 11 %. DM content was 48 %. A simple classification design with the previously mentioned treatments was employed. An analysis of variance was applied for the means of the productive indicators. The highest ADG (1.194 kg) was obtained in animals with an initial LW of 327 kg, although these did not differ from those starting with a LW of 282 kg and ADG of 1.076 kg. ADG decreased as LW increased (R2< 0.73). ADG in the group of 364 kg was 937 g and decreased as LW increased (R2 = 0.71 < 0.05), DM, ME and CP conversion increased with R2 value of 0.79 for these nutrients. In the group of animals of 422 kg, ADG was not affected and maintained constant until finishing the fattening with an average of 862 g. There was no difference from the group of 364 kg indicating that in high fiber diets, animals starting with LW higher than 350 kg, DM consumption stabilizes limiting ADG to values lower than 1 kg. Conversions in both groups of higher initial LW were worst than in those of lower LW. Data obtained demonstrate that with a 21:79 concentrate-fibrous feed relationship an ADG close to 1 kg is feasible. The forage contributes 78 % DM, 58 % CP and 65 % ME making possible the development of meat production technologies with agro-industrial fibrous residues.Key words: peanut cuticles, forage, fattening, stabulated, MUSS-Lactibiol